PROPOSAL TO CREATE STATE LEVEL BCIAS - DYER,DM (Tufts Archival Research Center, 2007)
Marginalia; Illegible/Difficult to Read; Memo from Dennis M. Dyer to Susan Stuntz regarding a proposal to create state Level BCIA's. States that businesses are reluctant to become involved in the IAQ/ETS issue. Indicates that this is possible to change if the right amount of resources and energy are put into it.